Hydraulic hammer drilling technology to replace air hammer drilling in deep BHE design - Thomson, Michael J. (2011)
Verkefnið er unnið í tengslum við Háskóla Íslands og Háskólann á Akureyri The following thesis addresses a few of the issues surrounding the geothermal energy sector of the renewables movement; how to drill deeper in order to utilize important geothermal potential? And, what to do with that potential once the depths have been reached? In order to arrive at this answer, a project originating at TU Darmstadt was taken as the main topic of interest for the analysis. The project is the design of drilling and completions for a deep borehole geothermal heat exchanger in the renovation of a building on campus. A combination of one dimensional heat transfer, FEM software analysis and literature studies on the existing drilling technology is used to guide these answers. The study and calculations show that hydraulic hammer drilling technology makes it possible to cheaply and effectively drill to depths of 800+ meters. Also a steel coaxial design of the heat exchangers allows for the transfer of nearly 150 W/m of thermal energy from a reservoir charged to 90oC. The collapse resistance of PVC and PE pipe limits the use of these materials for heat exchanger application. This study gives evidence that further research into hydraulic hammer drilling and borehole thermal energy storage could provide a promising future in the integration of cheap and effective alternate energy sources.